A Comparative Study of Retail price of fruits in Nepalgunj and Kathmandu - Daman Bahadur Singh, (Interdisciplinary Journal of Management and Social Sciences, 2022)
The main objective of this study is to compare the average price of fruits in Nepalgunj boarding India and Kathmandu very far from the border of India. This study is based on quantitative research design. Sample design is an on probability convenience sampling method. Unstructur questionnaire were used to collect data. Both descriptive and inferential statistical analytical methods were used to analyze data. The result of the analysis showed that the average price of fruits in the two cities was different and significate the average price of fruits in Nepalganj is higher than the average price of fruits in Kathmandu. The average price of seasonal and off seasonal fruits in Nepalganj and Kathmandu isRs.251.25 andRs.127.5 respectively Variation of the price of fruits in Kathmandu is 140.41and variation price in Nepalganj is 52.71 which shows that variation of price in Kathmandu is more than in Nepalganj because of the unstable demand for fruits in Kathmand the average price of fruits in Kathmandu is less than the average price of fruits in Nepalganj because fruits importers directly import fruits in Kathmandu and after that from Kathmandu fruits are distributed all over Nepal which increases transportation cost due to which the average price of fruits in Kathmandu is more than in Nepalganj.